IMPLEMENTASI METODE UP SELLING PADA SISTEM INFORMASI PENJUALAN - Novri Hadinata; Kurniawan Kurniawan; Inggri ramadanti utami (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
General Sudirman eye center is a clinic that is engaged in optics and pharmacies offer various types of eyewear items needed by customers. but sometimes customers find it difficult to choose the type of glasses they want and cannot know the price of similar items because there is no online website in the Sudirman eye center so customers must come directly to the clinic sometimes there is no recommendation system for goods from company employees to prospective customers, this results in the loss of opportunities for profit because customers may choose to buy elsewhere. This leads to consumer discontent with the service and has an impact on the decline in sales turnover, by building an online website that implements an up selling method which is a system to offer goods that are one level above that provides opportunities for prospective customers to choose products related to the product provided by the seller . Prospective customers who have chosen the product category will be given a choice of some similar or more expensive products.